The Impact of Bullying on Children’s Education and Mental Health at UPT SDN 325 Gresik - Rohmani, Abd. Hadi; Aini, Nur (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
Recently, there have been many cases of bullying that often occur in educational institutions. In this electronic era, bullying cases circulating on social media occur from middle school to high school levels. One of the places that should be the most protective and healthy place for children to seek knowledge is school. It's a shame that it has become a place of intimidation and violence. The aim of this research is to determine the impact of bullying on children's mental health and education at UPT SDN 325 Gresik and to find out what actions the school is taking to prevent bullying behavior. The techniques applied in this research are question and answer techniques, review and processing using qualitative methods. This research showed that there were acts of bullying that occurred at UPT SDN 325 Gresik. The impacts that occur are 1. Difficulty socializing, 2. Fear of coming to school, 3. Decreased learning achievement. The efforts made by schools to prevent bullying behavior include: 1. Moral cultivation, 2. Reprimand, 3. Advise, 4. Summons, 5. Punishment.